Hank the Heart and Animation‐Based Education for Pulmonary Hypertension - Michelle Cash; Barbara Giambra; Lara Stone; Melissa Magness; Kimberly Luebbe; Samantha Moore; Ryan Moore; Russel Hirsch; Kimberley Miles; Michael Kim; Paul J. Critser (Pulmonary Circulation, 2025)
ABSTRACT Pulmonary hypertension (PH) is a rare, complex disease affecting both children and adults. Efforts to provide health education are imperative as health literacy impacts patient and caregiver capacity to acquire, process, and understand health information and make informed health decisions. The current study sought to understand patient and family perception of “Hank the Heart”, an animation used for enhancing health literacy, and preferred learning methods for future educational preferences. A qualitative study was conducted to assess the “Hank the Heart” animation using focus groups of family caregivers and patients. Focus group and interview transcripts underwent inductive thematic analysis. Patients and families have complicated health and educational needs that require a personalized approach, and they identified with the animated character as a representation of their reality. We identified three primary themes: (1) An animated video was found to be helpful but not sufficient to address all caregiver and patient educational needs, (2) Parents and children resonated strongly with elements of the video that represent their own experiences, and (3) Patient and family centered ongoing and tailored education is needed. The use of animation videos as a form of education was well received. Patient and family insights and suggestions were offered for improving future animation development.